Java Assist Learning System for Assisted Learning on Facebook - Chien-Hung Lai; Wei-Ching Lin; Bin-Shyan Jong; Yen-Teh Hsia (2013 Learning and Teaching in Computing and Engineering (LaTiCE), 2013)
When students encounter learning difficulties in learning process, they often ask peers to find answer instead of asking teacher. But sometimes peers' ability is poor or ask question at wrong time, so they cannot get the answer immediately. And then they generate frustration of learning, thus lose their learning enthusiasm. In order to effectively improve the situation, to enable students can get answers in the shortest time. This study takes characteristics of the social network platform. The social network platform have advantage of notification and reminders, it allow students to get the answer immediately. Especially Facebook occupies the highest utilization rate in many social networking platforms. Facebook is very popular in recent years, it occupies a very high utilization rate of the Taiwan college students. Facebook boomed the research which been studying by many scholars. However, past studies mostly focused on the users use motivation of Facebook use application program of Facebook. There are been rarely explored about Facebook, especially in the educational aspects of application. Therefore this study use the function of Facebook as the tool, design a system about Java-Assisted Learning System (JALs) to help students learn programming. Because the system is built on Facebook, it let students can seek assistance immediately in the process of programming. The experimental results show that students not only give positive recognition for JALs, but also recognize the help about learning. And it can be seen, student who use JALs assisted learning system has the better learning achievements, it represents the JALs can enhance the effect of learning for students.